Mewujudkan Keluarga Berkualitas Melalui Edukasi dan Pengelolaan Dapur Sehat Cegah Stunting di Wilayah Pesisir Barat - Hamer, Welfarina; Handayana, Sri; Lisdiana, Anita; Purwasih, Atik (Pusat Pengabdian Masyarakat LPPM IAIN Metro, 2024)
This community service activity aims to increase community knowledge and understanding, especially in Paku Negara Village, Pesisir Barat Lampung, in preventing stunting, so that quality families can be realized for a better Indonesia. Stunting is a serious health problem in this area that can hinder the physical and mental development of children, so appropriate interventions are needed. This activity involves collaboration between the IAIN Metro community service team in collaboration with students from UM Metro Lampung university as well as health workers such as village midwives and posyandu cadres and local residents. The method used is PAR (Participatory Action Research), which is an activity carried out by involving villagers to jointly solve social problems that occur. Technically this activity includes socialization, implementation, combination / collaboration, education and realization (SIGER). The results of the community service activities are that the community knows information about stunting through socialization and educational leaflets that are distributed, the community knows the food menu with balanced nutrition through training in healthy kitchen management to prevent stunting and more and more people are aware of the importance of creating a quality family free of stunting because this program will continue even though this community service activity is over.